Indoor Companion Animal Poisoning by Plants in Europe - Bertero, Alessia; Fossati, Paola; Caloni, Francesca (Frontiers in Veterinary Science, 2020)
Indoor plant poisoning poses serious threats to companion animals. One of the major reasons of this kind of hazard can be identified in the increased amount of time that the pets spend indoor, sharing the domestic environment with their owners. In this review, the toxic houseplants most commonly associated with companion animal poisoning in Europe and well documented in the literature are emphasized. An analysis of the major and emerging plant species accountable for companion animal poisoning is proposed, in order to provide a framework of the factors influencing these incidents. Indeed, knowing the way substances may induce toxic effects in companion animals can be useful in allowing easier diagnosis and treatment processes. In conclusion, the Authors argue that a better characterization of the phenomenon, as well as of its extent, would be allowed by the availability of a centralized system for the data collection. Furthermore, better information and awareness on the issue may help developing a focused corrective approach to prevent indoor pet poisoning in Europe.